Analisis Yuridis Fenomena Kolom Kosong Pada Satu Pasangan Calon Pemilihan Kepala Daerah Di Kabupaten Banyumas Tahun 2024 (Studi Pada Komisi Pemilihan Umum Kabupaten Banyumas) - Firmansyah, Dimas; Ruhtiani, Maya; Afrilies, Marlia Hafny (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat 2025, 2025)
The phenomenon of a single candidate and the blank column in the 2024 Banyumas Regional Election raises debates about democratic legitimacy and legal certainty in Indonesia’s electoral system. This study employs a juridical-empirical method with a descriptive qualitative approach, combining literature review and interviews with Banyumas KPU commissioners to analyze the legal status of the blank column under Law No. 10 of 2016 and Constitutional Court Decision No. 100/PUU-XIII/2015, as well as to assess the legal responsibility of the Election Commission (KPU) in upholding democratic principles and popular sovereignty. The findings indicate that the blank column has constitutional legitimacy as a substantive democratic instrument that allows citizens to reject a single candidate. Empirically, the Banyumas KPU implemented the election process in accordance with the LUBER JURDIL principles, despite challenges such as regulatory gaps, unclear campaign rules for the blank column, and low levels of political literacy. Voter turnout reached 65,42%, with 40,56% voting for the blank column, reflecting growing political awareness and public criticism of elite dominance and weak party cadre regeneration. This study recommends regulatory reforms for single-candidate elections, strengthened political education, and optimization of political party roles in presenting competitive candidates to ensure a more substantive and equitable local democracy.